ANALISIS MAKNA POLISEMI VERBA MEMOTONG (KIRU) DALAM KALIMAT BAHASA JEPANG An Analysis of Polysemic Meaning of Verbs 'Cut (Kiru)' In Japanese - Abdul Gapur; Mhd. Pujiono (Metalingua: Jurnal Penelitian Bahasa, 2019)
Polysemy is a word that has more than one meaning. Not only limited to just one class of words, but polysemy is almost present in all classes of words. One of them is in kiru (切 る) verb. Kiru has the basic meaning 'cut' and has many meanings that often lead to errors in use, such as errors in translating Japanese sentences. Therefore in this research discussed the meaning of polysemi kiru verbs in Japanese sentences. This research is a qualitative research with descriptive method. The theory used is the theory of the expansion of contextual meaning and the polysemic meaning of Moriyama (2012). The data were obtained from sentences in discourses that used kiru verbs from various sources namely textbooks, novels and online newspapers. The results of this study were found 14 sentences in which there are kiru verbs. 13 sentences have the meaning of verb kiru cutting, dropping, opening, throwing, turning, starting, passing, actually already, stopping and breaking. But there is one sentence that occurs extension of meaning different the theory, namely the sentence shutta o kiru which means removing the shutter.